Quantifying avian relative abundance and ecosystem service value to identify conservation opportunities in the Midwestern U.S. - Chad B. Wilsey (Avian Conservation and Ecology, 2016)
Grassland birds are highly imperiled because of historical habitat loss and ongoing conversion of grasslands to agricultural and urban land uses. Therefore, prioritizing and further justifying conservation action in remaining grasslands is critical to protecting what remains. Grassland bird conservation has focused on identifying and protecting large grassland complexes referred to as Grassland Bird Conservation Areas (GBCAs). We identified and classified GBCAs in a region highly impacted by both agricultural and urban land conversion using previously developed methods. Then, we extended the analysis to include estimated relative abundance of five grassland focal species in each GBCA. Models of relative abundance were built using eight years of monitoring data collected by citizen scientists. Finally, we quantified the value of ecosystem services provided by each GBCA. There were nearly 55,000 ha of grassland habitats in the Chicago Metropolitan Region that met GBCA criteria, 33% (18,415 ha) of which were protected. Proportion of abundance in protected versus unprotected areas was similar for Bobolink (Dolichonyx oryzivorus; 46%), Grasshopper Sparrow (Ammodramus savannarum; 52%), and Sedge Wren (Cistothorus platensis; 48%), whereas, Henslow's Sparrow (Ammodramus henslowii; 75%) had a higher proportion of relative abundance in protected GBCAs and Eastern Meadowlark (Sturnella magna) had lower proportions (37%). GBCAs provisioned just under $900 million annually in ecosystem services, 73% of which is because of flood control. Outputs of this comprehensive approach will inform grassland bird conservation by providing detailed information about the value for birds and people of grassland habitats.